Earning Persistence Moderates the Influence of Corporate Social Responsibility, Conservative Accounting, and Growth Opportunity on Earnings Response Coefficient - Muhammad Ridho; Nofryanti; Holiawati (LP2M IAIN Palopo, 2026)
This study aims to analyze Purpose: the influence of Corporate Social Responsibility (CSR), accounting conservatism, and growth opportunity on the Earnings Response Coefficient (ERC), with earnings persistence as a moderating variable, in IDX80-listed companies over the 2021–2024 period. Methods: This research employs a quantitative approach using secondary data drawn from annual reports published on the official website of the Indonesia Stock Exchange (IDX). A purposive sampling technique yielded 42 companies and 168 firm-year observations. Data were analyzed using panel data regression, with model selection determined through the Chow Test, Hausman Test, and Lagrange Multiplier Test, followed by descriptive statistics, classical assumption tests, multiple linear regression, the F-test, the t-test, and Moderated Regression Analysis (MRA). Results: The results show that CSR and accounting conservatism do not significantly affect ERC, while growth opportunity has a significant effect on ERC; furthermore, earnings persistence moderates the relationship between CSR and ERC as well as between growth opportunity and ERC, but does not moderate the relationship between accounting conservatism and ERC. Implications: These findings imply that investors and analysts evaluating IDX80 firms should weigh growth opportunity and the persistence of reported earnings when interpreting earnings information, rather than relying on CSR disclosure or conservatism alone as signals of earnings quality, while for management and regulators they highlight that the market value of CSR initiatives may depend on the firm’s underlying earnings stability. Future research could extend the observation period, broaden the sample beyond IDX80, incorporate alternative measures of CSR, or test other potential moderating and mediating variables to deepen understanding of the determinants of the earnings response in the Indonesian capital market.